2018
DOI: 10.1155/2018/4582816
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Mutation Analysis of Patients with Best Vitelliform Macular Dystrophy or Autosomal Recessive Bestrophinopathy in Chinese Population

Abstract: Mutations in the gene BEST1 usually cause bestrophinopathies, such as the rare progressive diseases Best vitelliform macular dystrophy (BVMD) and autosomal recessive bestrophinopathy (ARB). This study aimed to investigate the clinical characteristics of patients with BVMD or ARB carrying BEST1 mutations. A total of 12 probands including 9 patients with a clinical diagnosis of BVMD and 3 patients with a clinical diagnosis of ARB were recruited for genetics analysis. All patients underwent detailed ophthalmic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 37 publications
(44 reference statements)
1
17
1
Order By: Relevance
“…Our work expands the pathogenic mutation spectrum of BEST1 associated with ARB and the clinical features of the disease, leading to improved diagnosis and genetic counseling criteria for affected patients and their families. In our study, missense mutations were the leading cause of ARB (5/7, 71%), which is in concordance with other reported cases [ 19 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our work expands the pathogenic mutation spectrum of BEST1 associated with ARB and the clinical features of the disease, leading to improved diagnosis and genetic counseling criteria for affected patients and their families. In our study, missense mutations were the leading cause of ARB (5/7, 71%), which is in concordance with other reported cases [ 19 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…Many studies, including this one, have attempted to determine genotype-phenotype correlations of Bestrophinopathy, but the evidence is limited [10,15]. However, we found that the homozygous BEST1 mutation spectrum has certain clinical characteristics, the most common being extrafoveal and extramacular yellowish subretinal deposits.…”
Section: Discussionmentioning
confidence: 71%
“…2008; Gao et al. 2018). Retinal oedema and neurosensory retinal detachment with subretinal fluid can be observed, and no vitelliform lesions develop 5 .…”
Section: Discussionmentioning
confidence: 99%
“…2012; Gao et al. 2018), and they have been investigated in several different ethnic groups (Italian, Dutch, Swedish, German, Chinese, Australian) (Deutman 1971; Tian et al. 2017; Gao et al.…”
Section: Discussionmentioning
confidence: 99%